Kuat Tekan Paving Block Limbah Plastik dengan Campuran Bahan Botol Air Mineral, Kantong Plastik dan Kemasan Plastik Bekas - Kalsum, Ummy; Agustina Dwiyanti,; Samsul,; Yanwar Samsul Akmal, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The increasing amount of plastic waste has become a major problem for the environment, requiring innovation in the utilization of such waste so that it has value, especially in the field of construction technology. The research objective of PENELITI Siremen UNIBA focuses on utilizing plastic waste by processing it into paving blocks to reduce environmental pollution for the sustainability of a healthy life. Based on the results of the the research, it was found that at 17 days, the average compressive strength of the paving blocks for each variation was as follows: variation 1 at 7.92 MPa, variation 2 at 7.92 MPa, variation 3 at 9.43 MPa, variation 4 at 4.66 MPa, variation 5 at 8.37 MPa, variation 6 at 9.79 MPa, and variation 7 at 6.68 MPa. Among all these variations, the 1BM:1KP:4KPB mixture showed the highest compressive strength and falls under Grade D according to the standard, which is typically used for lightduty applications. Based on these findings, it can be concluded that paving blocks made from plastic waste are only suitable for areas such as residential yards, in accordance with SNI 03-0691-1996 regulations.